2020
DOI: 10.1016/j.adolescence.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Growth and socio‐economic status, influence on the age at menarche in school going girls

Abstract: Introduction Onset age at menarche has been considered an important indicator of reproductive maturity in females and reflects the health status of the population. The purpose of this study was to determine the mean menarcheal age and to examine whether anthropometric and socio‐economic status (SES) influences age at menarche in the girls from Punjab province of Pakistan. Methods In this population‐based cross‐sectional study, 10,050 school‐going girls aged 8–16 years from 35 schools across 12 districts of Pun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Most of the studies from various geographical areas of Pakistan showed the age of menarche stabilized at the age of 11 to 13 year. 13,14 However recent study showed that most of the girls hit menarche when they were between 13-15 years old which is almost consistent with earlier reports of another study. 15 The result suggested that the prevalence of premenstrual symptoms (98%) is the highest among all menstrual abnormalities, which is supported by the results of another study.…”
Section: Discussionsupporting
confidence: 84%
“…Most of the studies from various geographical areas of Pakistan showed the age of menarche stabilized at the age of 11 to 13 year. 13,14 However recent study showed that most of the girls hit menarche when they were between 13-15 years old which is almost consistent with earlier reports of another study. 15 The result suggested that the prevalence of premenstrual symptoms (98%) is the highest among all menstrual abnormalities, which is supported by the results of another study.…”
Section: Discussionsupporting
confidence: 84%
“…Girls who reached menarche were found to be taller and heavier with a higher body mass index (BMI), and have a larger waist and hip circumferences compared to their pre-menarche counterparts. Girls with low socio-economic status (SES) experience delayed onset of menarche compared to those with medium/high SES [16]. In developed countries, the median age for menarche remains relatively stable-between 12 years and 13 years-across well-nourished populations.…”
Section: Resultsmentioning
confidence: 99%
“…Among the growth traits studied, the female who reached puberty were found to be heavier and taller, having a greater waist and hip circumference as compared to their prepuberty (Karim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence has suggested that obesity may delay the onset of puberty in boys, and accelerate the onset of puberty in girls (Soliman et al, 2014). Among the growth traits studied, the female who reached puberty were found to be heavier and taller, having a greater waist and hip circumference as compared to their prepuberty (Karim et al, 2021). Furthermore, weaning weight and weight of Bos indicus at puberty had significant positive effects on the manifestation of puberty (Monteiro et al, 2013).…”
Section: Discussionmentioning
confidence: 99%